2007
DOI: 10.1080/13625180701440818
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian multicentre prospective study on the effects of an oral contraceptive containing 3 mg drospirenone and 30 μg ethinyl oestradiol on somatic and psychological symptoms related to water retention and on body weight

Abstract: An oral contraceptive containing 3 mg DRSP and 30 microg EE significantly reduced the clinical symptoms of water retention. Body weight did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Indeed a recent extensive overview of the available clinical data has not found a causal relationship between hormonal contraceptives and body weight43. The increase of 0.35 kg reported for DRSP/EE over one year of treatment could be explained by the antimineralocorticoid action of DRSP, which results in some loss of body water in the first months of treatment38-44-45.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a recent extensive overview of the available clinical data has not found a causal relationship between hormonal contraceptives and body weight43. The increase of 0.35 kg reported for DRSP/EE over one year of treatment could be explained by the antimineralocorticoid action of DRSP, which results in some loss of body water in the first months of treatment38-44-45.…”
Section: Discussionmentioning
confidence: 99%
“…Mabrouk et al also described the possible beneficial effect of this regimen in patients with endometriosis [12]. The OCP with DRSP/EE possesses the advantages of the antimineralocorticoid activity reflected clinically in less fluid retention [13]. The beneficial effects of OCP with DRSP/EE on moderate acne [14] and premenstrual dysphoric disorder (PMDD) are well known and highly satisfactory [15].…”
Section: Introductionmentioning
confidence: 95%
“…Bloating and breast tenderness are, amongst weight gain and skin blemishes, parameters of the Moos Menstrual Distress Questionnaire for symptoms of water retention [11,12] Endrikat et al [13] showed that these symptoms decrease significantly in the premenstrual phase and to a lesser degree in the menstrual phase during treatment with DRSP/EE. Similar improvements were reported by other studies [14,15] Interestingly, Fruzzetti et al [15] demonstrated that total body water and intracellular water were significantly lower after treatment with DRSP/EE in women affected by premenstrual syndrome.…”
Section: Discussionmentioning
confidence: 99%